Legitimität als Herausforderung - Fehlmann, Fiona (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
Based on a mixed-methods approach, the book examines the legitimacy of Swiss public broadcasting among young audiences between of 14 and 35. Is this broadcaster perceived as important by these groups? And what significance do these groups have for the broadcaster? The central thesis: The legitimacy in question is disputed - for many, SRG SSR has a social value but little individual benefit. This circumstance challenges legitimacy. The SRG SSR is trying to adapt and will probably only have a future if it also has relevance in the personal everyday lives of young audiences.